4CPS-215 The impact of clinical pharmacist driven interventions on patient safety in hospitalised patients: preliminary results of a point prevalence study. (24th March 2020) - Wilkes, S; Zaal, R; Abdulla, A; Hunfeld, N
Abstract : Background and importance: Most patients admitted to a hospital use more than five drugs. Apart from the beneficial effects of these drugs, these patients are at risk of medication errors. Traditionally, hospital pharmacists use clinical decision support systems (CDSSs) and clinical rules to prevent drug related problems (DRPs). For specific instances, (eg, intensive care and paediatric care), it has been shown that the involvement of clinical pharmacists integrated into the medical team on the ward has a beneficial effect on the reduction in DRPs. Hence there is a shift from the traditional way of practice to integration of clinical pharmacists into the medical team on the ward. Aim and objectives: The aim was to investigate the impact of hospital-wide integration of clinical pharmacists on patient safety. Material and methods: In this observational point prevalence study, interventions made by clinical pharmacists (in addition to interventions based on clinical rules or CDSSs) were studied over 5 consecutive working days. Patients admitted for more than 24 hours were included. The following endpoints were recorded: type of intervention, reason for intervention, severity of the underlying DRP (using the NCC MERP index scale), proportion of interventions accepted by the physician, communication route and time investment. Results: A total of 238 medication reviews were conducted and the pharmacists were consulted 16 times. For 58.4% of the reviewed patients, potential DRPs were detected, with an average of 1.8 per patient. Overtreatment was the most reported DRP (31.6%) and subsequently the most common type of intervention was the advice to stop medication (43.2%). During the study, 16.0% of the interventions were categorised as no error, 62.0% as error, no harm and 22.0% as error, harm. Regarding acceptance, 66.6% of the interventions were accepted and given a follow-up. Face to face was the most frequently used method of communication (56.9%). The average time investment was 8.6 min per medication review. Conclusion and relevance: Structured medication reviews by clinical pharmacists contributed to detection and resolution of DRPs, mainly by reducing overtreatment. Therefore, in addition to clinical rules or CDSSs, a hospital-wide integration of clinical pharmacists as part of the multidisciplinary team can improve medication safety and optimise pharmaceutical care. References and/or acknowledgements: No conflict of interest.